ENaC subunit-subunit interactions and inhibition by syntaxin 1A - Berdiev, Bakhrom K.; Jovov, Biljana; Tucker, Ward C.; Naren, Anjaparavanda P.; Fuller, Catherine M.; Chapman, Edwin R.; Benos, Dale J. (American journal of physiology. Renal physiology, 2004)
Amiloride-sensitive epithelial Na + channels (ENaCs) are subject to modulation by many factors. Recent data have also linked the N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) machinery to this regulation of ENaC, but the molecular mechanisms that underlie this modulation are poorly understood. In this study, we demonstrate that syntaxin 1A physically interacts with ENaC and functionally regulates ENaC activity. Syntaxin 1A was able to coimmunoprecipitate in vitro-translated γ-ENaC, but not α- or β-ENaC. Also, using antibodies raised against α-, β-, or γ-ENaC, we detected syntaxin 1A in immunoprecipitates from Madin-Darby canine kidney cells stably transfected with αβγ-ENaC. In bilayers, syntaxin 1A inhibited ENaC, and this syntaxin 1A modulation of ENaC activity was eliminated by truncations of cytoplasmic domains of the ENaC subunits. Our findings provide evidence for a direct physical interaction between ENaC and syntaxin 1A and suggest involvement of ENaC's cytoplasmic domains in functional modulation of ENaC activity by syntaxin 1A.